Development and Evaluation of Steel Component Coatings for Substations/Converter Stations with Both Fire and Corrosion Prevention Functions - Yu Liu; Baohui Chen; Chuanping Wu; Tiannian Zhou; Bichen Pan (Fire)
There are a large number of steel components in substations/converter stations whose performance is seriously affected by being exposed to environmental corrosion and fire, endangering the operation of the substation/converter station. The current protective measures for steel components in substations/converter stations primarily involve the application of anti-corrosion and fireproof coatings. However, these coatings can easily peel off, resulting in a significant loss of their protective effectiveness. In response to this challenge, a new type of silicone-modified epoxy resin substrate has been synthesized by chemically grafting silicone resin onto epoxy resin segments, which retains the high adhesion of epoxy resin while enhancing its weather resistance. The use of synthesized nano zinc oxide-modified graphene oxide as a fireproof filler significantly improves the physical barrier effect and corrosion resistance of the coating. Additionally, the innovative addition of new metal anti-corrosion active pigments improves the adhesion and impermeability of the coating. Therefore, a steel structure coating for substations/converter stations with both fire and corrosion prevention functions has been developed. Standard tests conducted by national institutions have shown that the coating meets the performance requirements.